Features of biology аnd ecology Oestrus Ovis - I. O. Lysenko (Юг России: экология, развитие, 2015)
Are studied individual questions of biology, ecology O. ovis, its distributions in the conditions of sharp reduction of number of population of the owner. Intensity and extensiveness gadfly's inculcatijn are established, places of localisation of larvae of all age, daily and seasonal activity imago insects and their feature biological mutual relations with an organism of the owner on larval development stages is studied.